Demystifying Islam tackling the tough questions - Zafar, Harris (Rowman & Littlefied, 2014)
Despite heightened interest in the study of the Muslim faith, for many people Islam remains shrouded in mystery and confusion. Demystifying Islam offers refreshingly bold answers to provocative questions about Islam today.